When Should an Incumbent Be Obliged to Share its Infrastructure with an Entrant Under the General Competition Rules? - Mats Bergman (Uppsala University, Department of Economics, 2003)
According to the essential facilities doctrine, competition law requires an infrastructural monopoly to provide access. Under the Bronner criterion, proposed by the EC Court, the doctrine is only applicable when an infrastructural duopoly is non-viable. This paper uses a simple model to illustrate that, from a welfare point-of-view, the Bronner criterion may provide too little monopoly protection for the incumbent in high-risk new markets, while requiring too much investments from the entrant in moderately mature markets.
urn:nbn:se:uu:diva-4499
Keywords: L43; L51; 330; Infrastructure; access regulation; competition law; antitrust; Bronner; Infrastruktur; Netzregulierung; Wettbewerbsrecht